Mycobacterium tuberculosis-Induced Gamma Interferon Production by Natural Killer Cells Requires Cross Talk with Antigen-Presenting Cells Involving Toll-Like Receptors 2 and 4 and the Mannose Receptor in Tuberculous Pleurisy - Schierloh, Pablo (American Society for Microbiology (ASM), 2007)
Tuberculous pleurisy allows the study of human cells at the site of active Mycobacterium tuberculosis infection. In this study, we found that among pleural fluid (PF) lymphocytes, natural killer (NK) cells are a major source of early gamma interferon (IFN-γ) upon M. tuberculosis stimulation, leading us to investigate the mechanisms and molecules involved in this process. We show that the whole bacterium is the best inducer of IFN-γ, although a high-molecular-weight fraction of culture filtrate proteins from M. tuberculosis H37Rv and the whole-cell lysate also induce its expression. The mannose receptor seems to mediate the inhibitory effect of mannosylated lipoarabinomannan, and Toll-like receptor 2 and 4 agonists activate NK cells but do not induce IFN-γ like M. tuberculosis does. Antigen-presenting cells (APC) and NK cells bind M. tuberculosis, and although interleukin-12 is required, it is not sufficient to induce IFN-γ expression, indicating that NK cell-APC contact takes place. Indeed, major histocompatibility complex class I, adhesion, and costimulatory molecules as well as NK receptors regulate IFN-γ induction. The signaling pathway is partially inhibited by dexamethasone and sensitive to Ca(2+) flux and cyclosporine. Inhibition of p38 and extracellular-regulated kinase mitogen-activated protein kinase pathways reduces the number of IFN-γ(+) NK cells. Phosphorylated p38 (p-p38) is detected in ex vivo PF-NK cells, and M. tuberculosis triggers p-p38 in PF-NK cells at the same time that binding between NK and M. tuberculosis reaches its maximum value. Thus, interplay between M. tuberculosis and NK cells/APC triggering IFN-γ would be expected to play a beneficial role in tuberculous pleurisy by helping to maintain a type 1 profile.